Notes on the Homoneura subgenera Euhomoneura, Homoneura and Minettioides from China (Diptera: Lauxaniidae) - Shi, Li; Gaimari, Stephen D.; Yang, Ding (Zootaxa, 2012)
The proportion of the width of the lower margin of the face and the height of the gena is proposed to sort several speciesof Homoneura Wulp in the two subgenera Euhomoneura Malloch and Homoneura where the anteriormost dc is locatedat the transverse suture of the mesonotum. One species Homoneura (Homoneura) litorea sp. nov. is described as new toscience, and two species, Homoneura (Homoneura) stackelbergiana Papp and Homoneura (Minettioides) orientis (Hen-del) are recorded from China for the first time. The former species is elevated out of synonymy from Homoneura(Homoneura) stackelbergi Czerny. The species Homoneura alini Hering is synonymized under Homoneura (Homoneura)brevicornis Kertész. A key is presented to separate the five subgenera of Homoneura, and another key is presented to separate the Chinese species of the subgenera Euhomoneura and Minettioides Malloch.